2010
DOI: 10.1016/j.ejon.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of symptom clusters on functional status and quality of life in women with breast cancer

Abstract: Purpose The purposes of this study of women with breast cancer receiving chemotherapy with/without radiation therapy were to determine whether: 1) subgroups of oncology outpatients can be identified based on a specific symptom cluster (i.e., pain, fatigue, sleep disturbances, depression); 2) these subgroups differ on outcomes (i.e., functional status, quality of life; 3) subgroup membership changes over time. Methods A secondary data analysis using data collected from 112 women at initial chemotherapy. Sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
290
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(325 citation statements)
references
References 66 publications
(100 reference statements)
29
290
0
6
Order By: Relevance
“…Kim, et al, 2008;Ridner, 2005), researchers have also identified symptom clusters in patients with lung cancer (Fox & Lyon, 2006) and gliomas (Fox, Lyon, & Farace, 2007). Across studies of breast cancer patients, similar symptom clusters have emerged: researchers have identified clusters of fatigue, cognitive impairment, and mood disturbance (Bender, et al, 2005); fatigue, cognitive impairment, depressed mood, insomnia, and pain (H. Kim, et al, 2008); fatigue, depressed mood, and pain (Thornton, et al, 2010); and fatigue, pain, depression, and insomnia (Dodd, et al, 2010).…”
Section: Symptom Clusters In Cancermentioning
confidence: 94%
See 4 more Smart Citations
“…Kim, et al, 2008;Ridner, 2005), researchers have also identified symptom clusters in patients with lung cancer (Fox & Lyon, 2006) and gliomas (Fox, Lyon, & Farace, 2007). Across studies of breast cancer patients, similar symptom clusters have emerged: researchers have identified clusters of fatigue, cognitive impairment, and mood disturbance (Bender, et al, 2005); fatigue, cognitive impairment, depressed mood, insomnia, and pain (H. Kim, et al, 2008); fatigue, depressed mood, and pain (Thornton, et al, 2010); and fatigue, pain, depression, and insomnia (Dodd, et al, 2010).…”
Section: Symptom Clusters In Cancermentioning
confidence: 94%
“…Although breast cancer has been the cancer type most commonly studied for symptom clusters (Bender, et al, 2005;Dodd, et al, 2010;H. Kim, et al, 2008;Ridner, 2005), researchers have also identified symptom clusters in patients with lung cancer (Fox & Lyon, 2006) and gliomas (Fox, Lyon, & Farace, 2007).…”
Section: Symptom Clusters In Cancermentioning
confidence: 99%
See 3 more Smart Citations